ANALISIS PERSEPSI MAHASISWA GENERASI Z (GEN Z) TERHADAP NIAT MELAKUKAN WHISTLEBLOWING - Ulin Nuha Alfani; Fitri Mareta; Faila Suffah; Eksa Ridwansyah (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the perceptions of Generation Z (Gen Z) accounting students toward the intention to engage in whistleblowing. A questionnaire was used to collect the necessary information. The variables employed in this study include subjective norms, attitude toward behavior, perceived behavioral control, and reward as independent variables, while intention serves as the dependent variable. The study utilized purposive sampling for data collection, with a total of 160 samples. The respondents were accounting students from several public universities in Lampung Province, namely Lampung State Polytechnic, University of Lampung, Raden Intan State Islamic University, and Metro State Islamic Institute. The data were analyzed using Partial Least Squares (PLS). The results indicate that the variables of attitude toward behavior, perceived behavioral control, and reward have a positive influence on the intention of Generation Z accounting students to engage in whistleblowing. However, the subjective norm variable does not have a positive influence on their intention to whistleblow.